Bond, Favour Bank, and Social Capital: A Social-Scientific Reading of the Parable of the Dishonest Steward in Luke 16.1–9 - Uwaegbute, Kingsley Ikechukwu (Journal for the study of the New Testament, 2025)
Luke 16.1–9 is enigmatic. Many interpretative contexts have been offered to illuminate this parable. A social-scientific optic provides an interpretation mostly from the lens of shame, honour, generosity and a patron-client relationship. Reconsidering the parable from a social-scientific lens, this article proposes social capital theory as a good interpretative context, arguing that the dishonest debt reduction by the steward was simply a way through which he built social capital. Social capital building was not new in the Greco-Roman world; it was practised among groups of people to solidify ‘favour banking’, which explains why the master praised the steward’s action since he was aware that such ‘favour banking’ was possible in their world. Jesus then adopted the same position and tasked his disciples to build social capital, to solidify relationships with others by doing favours to them so that when in need, such favours would be returned to them.